Functional characterization of GhSOC1 and GhMADS42 homologs from upland cotton (Gossypium hirsutum L.). (January 2016) - Zhang, Xiaohong; wei, Jianghui; Fan, Shuli; Song, Meizhen; Pang, Chaoyou; Wei, Hengling; Wang, Chengshe; Yu, Shuxun
Highlights: Overexpression of GhSOC1 and GhMADS42 promoted flowering and abnormal flower organ. GhSOC1 may bind to the promoter of GhMADS41 and GhMADS42 to regulate flowering. GhSOC1 could interact with AP1/FUL-like proteins in cotton. Abstract: In Arabidopsis flowering pathway, MADS-box genes encode transcription factors, with their structures and functions highly conserved in many species. In our study, two MADS-box genes GhSOC1 and GhMADS42 ( Gossypium hirsutum L.) were cloned from upland cotton CCRI36 and transformed into Arabidopsis . GhSOC1 was additionally transformed into upland cotton. Comparative analysis demonstrated sequence conservation between GhSOC1 and GhMADS42 and genes of other plant species. Tissue-specific expression analysis of GhSOC1 and GhMADS42 revealed spatiotemporal expression patterns involving high transcript levels in leaves, shoot apical buds, and flowers. In addition, overexpression of both GhSOC1 and GhMADS42 in Arabidopsis accelerated flowering, with GhMADS42 transgenic plants showing abnormal floral organ phenotypes. Overexpression of GhSOC1 in upland cotton also produced variations in floral organs. Furthermore, chromatin immunoprecipitation assay demonstrated that GhSOC1 could regulate GhMADS41 and GhMADS42, but not FLOWERING LOCUS T, by directly binding to the genes promoter. Finally, yeast two-hybrid and bimolecular fluorescence complementation approaches were undertaken to better understand the interaction of GhSOC1 and other MADS-box factors. These experiments showed that GhSOC1 can interact with APETALA1/FRUITFULL-like proteins in cotton.